2014
DOI: 10.1016/j.enbuild.2012.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Spatial planning as a driver of change in mobility and residential energy consumption

Abstract: a b s t r a c tThis paper analyses the impact of territorial structures upon energy consumption in the Walloon Region (Belgium). The rationale for this research is to consider the long-term influence of spatial planning decisions upon energy consumption in both residential building stock and home-to-work commuting. The analysis has been conducted on a regional scale (16,844 km 2 ) and includes urban, peri-urban and rural settlements. Those settlements that perform well in mobility also appear to perform well i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…The reason behind this high percentage of insulation level in glazing area is that (France-Laure et al, 2011). The same fact has also been supported by the decreasing heating energy requirement for the buildings over the period of time (Table 6) (Dujardin et al, 2010(Dujardin et al, , 2013Walloon Government, 2007). Table 6 represents the heating energy consumption per year of the building stock over the years.…”
Section: Building Energy Performance Analysismentioning
confidence: 70%
See 2 more Smart Citations
“…The reason behind this high percentage of insulation level in glazing area is that (France-Laure et al, 2011). The same fact has also been supported by the decreasing heating energy requirement for the buildings over the period of time (Table 6) (Dujardin et al, 2010(Dujardin et al, , 2013Walloon Government, 2007). Table 6 represents the heating energy consumption per year of the building stock over the years.…”
Section: Building Energy Performance Analysismentioning
confidence: 70%
“…It is also found from the data base that in Walloon region the external walls of 91% and roof of 78% of houses are not insulated. It is observed from the temperature profile of Liege that most of the time of the year heating is required and the same fact is being supported by the relatively high heating degree days of Liege (Table 6) (Dujardin et al, 2010(Dujardin et al, , 2013Walloon Government, 2007).…”
Section: Building Energy Performance Analysismentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, many methods including geographically weighted regression [33] and spatial correlation analysis [34] were introduced. Dujardin et al [35] analyzed the impact of territorial structures upon energy consumption in the Wakkoon Region and revealed that some rural settlements characterized by low density show good performance in terms of energy efficiency. Li et al [36] described the spatial dynamic distribution of heavy metals by using GIS; and Mua et al [37] also used GIS to analyze the distribution of species.…”
Section: Related Studiesmentioning
confidence: 99%
“…Topographically, elevations in the region range from sea level to 693 m above sea level. Wallonia is characterized by a strong sprawl and the resulting landscape fragmentation (Dujardin et al, 2014;EEA, 2011). Densification strategies are especially important in such a context so as to limit the further consumption of land and to better structure existing peri-urban areas considering their specificities (De Smet and Teller, 2016).…”
Section: Study Areamentioning
confidence: 99%